Identification of MicroRNAs in Taxillus chinensis (DC.) Danser Seeds under Cold Stress. (30th May 2021) - Fu, Jine; Wan, Lingyun; Song, Lisha; He, Lili; Jiang, Ni; Long, Hairong; Huo, Juan; Ji, Xiaowen; Wei, Ying; Wei, Shugen; Pan, Limei
Abstract : Taxillus chinensis (DC.) Danser, a parasitic plant that belongs to the Loranthaceae family, has a long history of being used in the Chinese medicine. We observed that the loranthus seeds were sensitive to temperature and could lose viability below 0°C quickly. Thus, we performed small RNA sequencing to study the microRNA (miRNA) regulation in the loranthus seeds under cold stress. In total, we identified 600 miRNAs, for the first time, in the loranthus seeds under cold stress. Then, we detected 224, 229, and 223 miRNAs (TPM > 1 ) in A0 (control), A1 (cold treatment for 12 h at 0°C), and A2 (cold treatment for 36 h at 0°C), respectively. We next identified 103 differentially expressed miRNAs (DEmiRs) in the loranthus seeds in response to cold. Notably, miR408 was upregulated during the cold treatment, which can regulate genes encoding phytocyanin family proteins and phytophenol oxidases. Some DEmiRs were specific to A1 and may function in early response to cold, such as gma-miR393b-3p, miR946, ath-miR779.2-3p, miR398, and miR9662. It is interesting that ICE3, IAA13, and multiple transcription factors (e.g., WRKY and CRF4 and TCP4) regulated by the DEmiRs have been reported to respond cold in other plants. We further identified 4, 3, and 4 DEmiRs involved in the pathways "responding to cold, " "responding to abiotic stimulus, " and "seed development/germination, " respectively. qRT-PCR was used to confirm the expression changes of DEmiRs and their targets in the loranthus seeds during the cold treatment. This is the first time to study cold-responsive miRNAs in loranthus, and our findings provide a valuable resource for future studies.